Long-term noninvasive single photon emission computed tomography monitoring of perfusional changes after EC-IC bypass surgery. Issue 8 (August 1987) - Di Piero, V; Lenzi, G L; Collice, M; Triulzi, F; Gerundini, P; Perani, D; Savi, A R; Fieschi, C; Fazio, F
Abstract : The rCBF was evaluated using I-123 HIPDM and single photon emission computed tomography (SPECT) on 14 patients undergoing extracranial-intracranial (EC-IC) bypass surgery because of internal carotid artery (ICA) occlusion. Before surgery, all patients showed cortical areas of hypoperfusion over the affected cerebral hemisphere. Shortly after EC-IC bypass a rCBF increase was observed in six patients. However, at the 6 and 12 month follow-ups, with angiographic control of bypass patency, rCBF studies did not show any significant rCBF change. Long-term noninvasive tomographic monitoring of perfusion changes occurring after EC-IC bypass surgery failed to show a long-lasting improvement in perfusion.